Soils, microbes, and forest health: A qualitative analysis of social and institutional factors affecting genomic technology adoption. (November 2015) - Crann, Sara E.; Fairley, Cory; Badulescu, Dan; Mohn, William W.; O'Doherty, Kieran C.
Abstract: Within the forestry sector in British Columbia, a variety of methods exist for evaluating forest health. While the definition of forest health and the establishment of appropriate metrics for assessment have been debated, there is little disagreement among scientists and forestry practitioners on the importance of soil in assessing and maintaining healthy forests. Advances in genomic science now permit in-depth analysis of soil microbial communities, which can be used to assess various aspects of forest health. The translation of genomic microbial science to future technical developments can make soil microbial analysis practical and economical for forest management practices. Drawing on theories of technology adoption, this paper examines the social and institutional aspects of forestry in British Columbia to develop an understanding of the context in which a novel soil microbial genomic technology would be situated. This study draws on a series of interviews conducted with practitioners and stakeholders in the British Columbia forestry sector. Our findings suggest that while there is considerable interest in genomic microbial technology for forest health assessment, several key challenges will impact the practical application of this technology. Highlights: Forestry experts were receptive to the idea of new tools to assess forest health. Forest health is an ambiguous concept, which may be a barrier for new technology. Users must be able understand the technology in order to use it. New technology for forest health assessment must be efficient. New technology for forest health assessment must be cost-effective.